A Novel Mutation (D395A) in Valosin-Containing Protein Gene Is Associated With Early Onset Frontotemporal Dementia in an Italian Family - Bruno, Francesco; Conidi, Maria Elena; Puccio, Gianfranco; Frangipane, Francesca; Laganà, Valentina; Bernardi, Livia; Smirne, Nicoletta; Mirabelli, Maria; Colao, Rosanna; Curcio, Sabrina; Di Lorenzo, Raffaele; Maletta, Raffaele; et al. (Frontiers in Genetics, 2021)
Inclusion Body Myopathy (IBM) with Paget’s Disease of Bone (PDB) and/or Frontotemporal Dementia (FTD) (IBMPFD) was recently identified as rare autosomal dominant disorder due to mutations in VCP gene. However, VCP mutations have also been documented in patients with Amyotrophic Lateral Sclerosis (ALS), Charcot-Marie-Tooth type 2 (CMT2) disease and Hereditary Spastic Paraplegia (HSP), underlining the heterogeneity of the phenotypes due to VCP mutations. In this work, we reported a novel missense heterozygous variant c.1184A>C (p.D395A) in exon 10 of VCP gene identified in three patients (two sisters and one brother) belonging to an Italian family. The patients underwent a detailed clinical evaluation including medical history, neurological examination and neuropsychological assessment. Brain morphologic and functional analysis were also performed. The whole picture was consistent with the criteria of Behavioral Variant Frontotemporal Dementia (bvFTD) without IBM and PBD. Our report confirms the high degree of heterogeneity of VCP-disease. VCP analysis should be considered for the genetic screening of familial bvFTD with an early onset also in absence of IBM or PDB signs.